2017
DOI: 10.3354/meps12201
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem services are lost when facilitation between two ecosystem engineers is compromised by oil

Abstract: Nearshore marine ecosystems are among the most productive areas in the world. Unfortunately, these areas also receive pollutants released into oceanic and riverine waters. Six years following the Deepwater Horizon oil spill, the largest in US history, the complexity of ecological injuries in this system is just now being elucidated. Here, we describe a novel pathway of injury from oil spills by documenting how the loss of oysters near marsh edge as a direct result of shoreline oiling and clean-up activities ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Some impacts, however, were severe and obvious. For sedentary species including Eastern Oyster the combination of the toxicity of oil and the effects of freshening the marshes not only resulted in mass oyster mortalities (Powers et al, 2017a), but oiling of the marshes was also was associated with collapse of the marsh edges and the loss of oyster bars, which in turn resulted in increased soil erosion and other negative consequences for marsh ecosystems (Grabowski et al, 2012;Powers et al, 2017c;Hughes et al, 2018). Likewise, Bottlenose Dolphins' exposure to toxic oil concentrations presented a variety of negative health effects including reduced reproduction and associated morbidities and mortalities (Schwacke et al, 2014(Schwacke et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some impacts, however, were severe and obvious. For sedentary species including Eastern Oyster the combination of the toxicity of oil and the effects of freshening the marshes not only resulted in mass oyster mortalities (Powers et al, 2017a), but oiling of the marshes was also was associated with collapse of the marsh edges and the loss of oyster bars, which in turn resulted in increased soil erosion and other negative consequences for marsh ecosystems (Grabowski et al, 2012;Powers et al, 2017c;Hughes et al, 2018). Likewise, Bottlenose Dolphins' exposure to toxic oil concentrations presented a variety of negative health effects including reduced reproduction and associated morbidities and mortalities (Schwacke et al, 2014(Schwacke et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Relative positions of different years are determined by Bray-Curtis similarities between all possible pairings of years, with 2D stress reflecting the extent of distortion (low distortion, in this case) created by representing these Bray-Curtis similarities in a two-dimensional Euclidean space. cover declined >99% at oiled sites as opposed to unoiled ones (Grabowski et al, 2017;Powers et al, 2017c), an effect that persisted for several years after the DWH event.…”
Section: Species-level Summariesmentioning
confidence: 94%
“…In contrast, Alabama filled a breach along a barrier island, elevating salinity in Mississippi Sound [ 7 8 ]. Mechanical methods were also used to remove visible oil from estuarine habitats [ 9 ]. Therefore, nearshore ecosystems were likely subjected to multiple stressors including oil, dispersants, and atypical salinity regimes during the response period.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers in this Theme Section highlight the complexity of effects that occur when habitat-forming species are injured by oiling or associated response activities. For example, Powers et al (2017a) demonstrated how the loss of fringing oyster reef as a result of the oil spill can accelerate coastal erosion of marsh habitat. Changes in the quantity and quality of essential habitats will directly affect many ecosystem services (e.g.…”
Section: Recovery Of Nearshore Ecosystems From the Dwhosmentioning
confidence: 99%
“…Studies published in this Theme Section and elsewhere expand upon the paradigms already established based on the Exxon Valdez oil spill on nearshore communities and show that: (1) organismal effects of heavy oiling occur across the full range of trophic levels; (2) oiling of foundational species or 'ecosystem engineers' can result in complex and long-term direct and indirect negative effects on nearshore ecosystems (Peterson et al 2003); (3) ecological injury to biogenic habitats can result in loss of ecosystem services that cascade and affect other habitats and processes (Powers et al 2017a); and (4) shoreline response activities intended to remove or mitigate the effects of oil are also associated with negative impacts on habitat-forming species (Driskell et al 2001, Martínez et al 2012, Peterson et al 2012, Grabowski et al 2017, Michel et al 2017, this Theme Section, Powers et al 2017a.…”
Section: Recovery Of Nearshore Ecosystems From the Dwhosmentioning
confidence: 99%